2019
DOI: 10.1186/s12909-018-1418-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of critical thinking disposition on the learning efficiency of problem-based learning in undergraduate medical students

Abstract: BackgroundProblem-based learning (PBL), a pedagogical approach, is widely accepted in medical education. Manipulated by many factors, the internal motivation of learner is the most crucial determinant that affects the nature of the outcome, in which the influences of critical thinking (CT) remained elusive.MethodsOne hundred two third-year undergraduate medical students at Peking University were involved in this study. A Chinese version of the Critical Thinking Disposition Inventory (CTDI-CV) was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 31 publications
(37 reference statements)
4
100
0
9
Order By: Relevance
“…Students met or exceeded the 40-point cut on the open-mindedness, analyticity, inquisitiveness, and cognitive maturity subscales. Similar to other studies, inquisitiveness was found to score the highest [7,36]. High scores for inquisitiveness indicated a greater potential for the improvement of CT and clinical practice capabilities.…”
Section: The Status Of Ctsupporting
confidence: 86%
See 1 more Smart Citation
“…Students met or exceeded the 40-point cut on the open-mindedness, analyticity, inquisitiveness, and cognitive maturity subscales. Similar to other studies, inquisitiveness was found to score the highest [7,36]. High scores for inquisitiveness indicated a greater potential for the improvement of CT and clinical practice capabilities.…”
Section: The Status Of Ctsupporting
confidence: 86%
“…Health professionals need to effectively cope with complex and demanding clinical situations in fast rhythm environments. Medical workers need advanced CT skill to accomplish actions that directly affect patient results [7,8]. These actions include analyzing patients' cases, considering patients' emotions and weighing possible therapeutic measures, then recognizing which treatment is the most appropriate [9].…”
Section: Introductionmentioning
confidence: 99%
“…More targeted outcome measures might show stronger relationships with aspects of critical thinking. For instance, a study of medical students found that performance on problem‐based learning exercises correlated positively with critical thinking disposition, and a study involving medical residents showed that concept mapping ability is associated with critical thinking . Since critical thinking does not necessarily correspond to academic achievement, there has been a movement toward authentic assessment, which places critical thinking appraisal in the context of simulated scenarios or actual patient care settings …”
Section: Discussionmentioning
confidence: 99%
“…All the students showed positive scores in CCTDI with an average of 297.72. CCTDI score showed also positive correlation with the PBL evaluation scores [17]. Furthermore, the performance of 193 medical students at Al Nafees medical school, Islamabad, Pakistan in a higher cognitive and clinical reasoning exam was improved after one-year PBL program [18].…”
Section: Discussionmentioning
confidence: 99%